Genetic characterization of four Brazilian states with 25 Yfiler®Plus markers - Jannuzzi, J.; Alho, C. S.; Fridman, C.; Ferreira, S. R.B.; Braganholi, D. F. [UNESP]; Ambrosio, I. B. [UNESP]; Cicarelli, R. M.B. [UNESP]; Gomes, V.; Carvalho, E. F.; Gusmão, L. (Elsevier, 2017)
The Y-STRs have high mutation rates, being useful to discriminate unrelated males. They are widely used in paternity and forensic investigations to study the recent history and migration movements of populations. Recently, the YfilerPlus was released to increase discrimination inside populations, by adding 9 Y-STRs to the previous Yfiler version. The genetic composition of Brazil is known to vary through 5 geopolitical regions: South, Southeast, North, Northeast and Central-west. Therefore, for this study, samples from Maranhão, Espírito Santo, São Paulo and Rio Grande do Sul were characterized for the Y-STR markers present in YfilerPlus kit, to evaluate if diversity increases with the enlargement of the Yfiler set, and if significant differences exists among populations. Genetic differentiation analysis did not reveal statistically significant differences in the YfilerPlus haplotype composition of the studied samples. High diversities were observed in all samples for both Yfiler and YfilerPlus marker sets. Inside populations, 20 haplotypes were shared by two individuals for the Yfiler-STRs. This number decreases to 14 when using the 25 Y-STRs from the YfilerPlus. The YfilerPlus demonstrated an increased discrimination power in comparison to the Yfiler kit, being suitable for forensic applications in the studied Brazilian populations, for which data were not yet available.
Keywords: Admixed populations; Brazil; Haplotype diversity; South America; Y-STRs